"That Heart Sickness": Young Aboriginal People's Understanding of Rheumatic Fever. Issue 1 (2nd January 2019) - Mitchell, Alice G.; Belton, Suzanne; Johnston, Vanessa; Gondarra, Wopurruwuy; Ralph, Anna P.
ABSTRACT: High rates of acute rheumatic fever (ARF) and rheumatic heart disease (RHD) in Australia predominate in young Aboriginal people highlighting underlying racial and equity issues.  This article focuses on the perceptions of the disease among young Aboriginal people living in remote Australia. Participant understanding was constrained by clinicians' use of language rooted in biomedicine and delivered through English, a second language for all participants. Clinicians' communicative competency is a social determinant of Aboriginal health. We recommend that the use of Aboriginal languages be prioritized in health services caring for Aboriginal people and that biomedical dominance in the services be relinquished.